A model describing the pressure drops across the membrane and cake layers for constant flux cross-flow microfiltration process. Issue 3 (June 2022) - Gao, Shujuan; Zhong, Chenyin; Wang, Zhan
Abstract: A combined model (pore-blocking/shrinking-cake filtration) was established based on the Darcy's law, Hagen-Poiseuille equation and classic blocking law to study the fouling behavior of a 0.1 µm PAN membrane fouled with the extracellular polymer substance model solution (bovine serum albumin (BSA), sodium alginate (SA) and humic acid (HA)) under different operating conditions in the constant flux cross-flow filtration process. Results showed that the model predictions had good agreements with experimental data not only for single component solution (BSA, SA and HA), but also for the binary mixtures (BSA+SA, BSA+HA and SA+HA), ternary mixtures (BSA+SA+HA) and other membranes (0.1 µm PES and PVDF) (R 2 ≥ 0.874). The dominant fouling mechanism is pore-blocking/shrinking at lower concentration, lower flux, or higher velocity in the whole stage. In contrast, the dominant fouling mechanism is pore-blocking/shrinking-cake formation in the first stage while it is cake formation in the second stage at a higher concentration, higher flux, or lower velocity. Meanwhile, the trans-membrane pressure ( P ) increased rapidly in the first stage for both situations while P kept constant for the first situation and P increased slowly for the second situation in the second stage. Furthermore, transition point and time from combined mechanism to individual mechanism were determined. This model can provide guides for industrial backwashing processes. Highlights: A new model was established for the constant flux cross-flow filtration process. The total pressure drop can be divided into membrane/cake layer pressure drops. Transition points and duration of the fouling mechanism were determined. The available membrane area ratio and detailed resistance were analyzed.